Application of BDD and DSA electrodes for the removal of RB 5 in batch and continuous operation. (June 2017) - Soni, B.D.; Patel, U.D.; Agrawal, A.; Ruparelia, J.P.
Abstract: The experiments on removal of Reactive black 5 (RB 5) dye were performed in batch and continuous operation using boron doped diamond (BDD) and dimensionally stable anode (DSA) electrodes. The electrooxidation of simulated wastewater was carried out in aqueous medium of pH 2 containing 100 mg/L RB 5 on Si/BDD and Nb/BDD electrodes. For batch degradation studies of RB 5, 50 mA/cm 2 current density was applied in the presence of 4 g/L NaCl as supporting electrolyte. The electrolysis was performed on both the BDD electrodes with each electrode having effective area of 25 cm 2 . As a result of batch operation, almost 99% decolourization and 90% chemical oxygen demand (COD) removal was observed after 30 min of electrolysis due to electrooxidation on non-active anodes. Further, an attempt was made to degrade RB 5 using three tanks in series in continuous operation under identical operating conditions of batch process. For this operation, two Ti/PtOx -RuO2 -SnO2 -Sb2 O5 electrodes were equipped in first two tanks while third tank was operated with Si/BDD and Nb/BDD one after another. The effects of constant flow rate of 30 mL/min were evaluated for removal of colour, COD and total organic carbon (TOC) from aqueous solution of RB 5 azo dye. As a consequence of electrolysis, 99% colour removal, 95% COD removal and more than 70% TOC removal were observed. Characterization of the electrodes were carried out for surface morphology analysis by scanning electron microscopy (SEM), surface structure analysis was performed by x-ray diffraction (XRD) while electrochemical behaviour was observed by cyclic voltammetry techniques.